Orbital volume and shape in Treacher Collins syndrome. Issue 2 (February 2018) - Levasseur, Julie; Nysjö, Johan; Sandy, Ronak; Britto, Jonathan A.; Garcelon, Nicolas; Haber, Samer; Picard, Arnaud; Corre, Pierre; Odri, Guillaume A.; Khonsari, Roman H.
Abstract: Orbito-palpebral reconstruction is a challenge in Treacher Collins syndrome (TCS). This study investigates orbital phenotypes in TCS using cephalometry and orbital shape analysis. Eighteen TCS and 52 control patients were included in this study, using the Dr Warehouse database. Orbital cephalometry was based on 20 landmarks, 10 planes, 16 angles, and 22 distances. Orbits were segmented. Registration-based, age-specific mean models were generated using semi-automatic segmentation, and aligned and compared using color-coded distance maps – mean absolute distance (MAD), Hausdorff distance (HD), and Dice similarity coefficient (DSC). Symmetry was assessed by mirroring and DSC computing. Central orbital depth (COD) and medial orbital depth (MOD) allowed 100% of orbits to be classified. COD and lateral orbital depth (LOD) were different from the controls. Average MAD between TCS and controls was ≤1.5 mm, while for HD it was >1.5 mm, and for DSC <1. TCS orbits were more asymmetrical than controls, and orbital volumes were smaller when age was considered as a confounding factor, and had a trend for normalization with age. This report emphasizes the importance of combining different morphometric approaches in the phenotype characterization of non-trivial structures such as the orbit, and supports composite skeletal and soft-tissue strategies for the management of the peri-orbital region.